Creation of a gamefish occurrence dataset from public-focused informational newsletters - Hedreen, Rebecca; Grace, Sean (2019 NEAFWA Conference, 2019)
Fish and wildlife agencies produce a bounty of information aimed at the public. Under the right circumstances, that information can be compiled into scientifically useful data to complement full scientific studies. This poster describes some preliminary results from a project to compile mentions of gamefish species, locations, and sizes throughout the Long Island Sound and surrounding waters from the Weekly Fishing Report (2006, 2008-2018) and the Trophy Fish Report (2009-2017), both produced by the Connecticut Dept. of Energy and Environmental Protection. The dataset consists of more than 20,000 entries from the reports collected weekly by DEEP employees from tackle shops and charter companies. The current portion of the analysis is to determine the characteristics of the dataset, such as entry types, species counts, and some general trends. Presented at the 2019 NEAFWA Conference in Groton, CT and the 2019 CSCU Faculty Research Conference at SCSU in New Haven, CT.
Keywords: Coastal fisheries; Connecticut; Data collections; Estuarine fisheries; Fish catch statistics; Game fish; Geographical coordinates; Geographical distribution; Life Sciences; Long Island Sound; Marine Biology; Sport fishing statistics; dept.bio; dept.lib